Social climate on tobacco control in an advanced tobacco control country: A population-based study in Finland - Ruokolainen, Otto (Nordisk Alkohol Nark, 2018)
AIMS: Finland has implemented a gradually tightening tobacco control policy for decades. Recently the objective of a tobacco-free Finland was introduced. Still, the population’s acceptance of tobacco control policy has not been measured. More knowledge is needed on differences in attitudes and factors associated with tobacco control opinions for future policy-making. METHODS: A population-based study with quantitative analysis. Attitudes on smoking and tobacco control policy were assessed within the National FINRISK 2012 Study in Finland involving 25–74-year-old adults (N = 4905). In analyses, smoking status groups were compared. RESULTS: In general, attitudes differed systematically by smoking status. Differences increased or decreased when moving from never smokers to other smoking groups. Similarities in attitudes were found particularly on youth smoking, while differences between smoking groups were notable on statements regarding smoking on balconies and availability of tobacco products. The adjusted analysis showed that smoking status was most strongly associated with attitudes on different tobacco control policy measures. Daily smokers viewed stricter tobacco control policy and workplace smoking bans more negatively than others, though they viewed societal support for quitters and sufficiency of tobacco control policy more positively compared with others. Differences were vast compared with non-smokers, but also occasional smokers differed from daily smokers. CONCLUSIONS: Tightening tobacco control and workplace smoking bans were supported by the Finnish adult population, but societal support for quitters to a lesser extent. Attitude change, where smokers are seen as deserving help to quit smoking, is important.